2D Transition Metal Dichalcogenides: Design, Modulation, and Challenges in Electrocatalysis. Issue 6 (24th June 2020) - Fu, Qiang; Han, Jiecai; Wang, Xianjie; Xu, Ping; Yao, Tai; Zhong, Jun; Zhong, Wenwu; Liu, Shengwei; Gao, Tangling; Zhang, Zhihua; Xu, Lingling; Song, Bo
Abstract: Hydrogen has been deemed as an ideal substitute fuel to fossil energy because of its renewability and the highest energy density among all chemical fuels. One of the most economical, ecofriendly, and high‐performance ways of hydrogen production is electrochemical water splitting. Recently, 2D transition metal dichalcogenides (also known as 2D TMDs) showed their utilization potentiality as cost‐effective hydrogen evolution reaction (HER) catalysts in water electrolysis. Herein, recent representative research efforts and systematic progress made in 2D TMDs are reviewed, and future opportunities and challenges are discussed. Furthermore, general methods of synthesizing 2D TMDs materials are introduced in detail and the advantages and disadvantages for some specific methods are provided. This explanation includes several important regulation strategies of creating more active sites, heteroatoms doping, phase engineering, construction of heterostructures, and synergistic modulation which are capable of optimizing the electrical conductivity, exposure to the catalytic active sites, and reaction energy barrier of the electrode material to boost the HER kinetics. In the last section, the current obstacles and future chances for the development of 2D TMDs electrocatalysts are proposed to provide insight into and valuable guidelines for fabricating effective HER electrocatalysts. Abstract : Transition metal dichalcogenides (TMDs) are considered to be promising candidates over noble metal catalysts for electrochemical hydrogen production. The basic mechanism for the hydrogen evolution reaction (HER) is introduced, followed by a description of the different synthesis methods and modulation approaches to enhance the catalytic performance of TMD‐based catalysts toward the HER.